PENGARUH DEBT COVENANT , BONUS PLAN , POLITICAL COST DAN RISIKO LITIGASI TERHADAP PENERAPAN KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR - Sulastiningsih Sulastiningsih; Jaza Anil Husna (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
This study aims to examine the influence of debt covenants, bonus plans, political costs, and litigation risks to accounting conservatism. Accounting conservatism is the dependent variable in this study which is measured by total accrual (before depreciation). The independent variables in this research include debt covenant, bonus plan, political cost, and litigation risk. The sample of this study is a manufacturing company listed on the Indonesia Stock Exchange during the period of 2010-2014. The sample in this study is determined by using purposive sampling method. The samples obtained in this research are 22 companies. Hypothesis testing is done by using multiple linear regression analysis method. Based on hypothesis test, it is concluded that the debt covenant variable proxied with leverage has no influence on accounting conservatism. Bonus plans proxied with managerial ownership structure have no significant influence on accounting conservatism. Political costs proxied with the firm size do not significantly influence accounting conservatism. The risk of litigation proxied with the firm measurement in terms of assets growth significantly influence accounting conservatism